2015
DOI: 10.1053/j.gastro.2015.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Bradycardia After First Doses of Sofosbuvir and Daclatasvir in Patients Receiving Amiodarone: 2 Cases Including a Rechallenge

Abstract: Sofosbuvir and daclatasvir are direct-acting antiviral drugs used to treat chronic hepatitis C virus infection. In 2015, the Food and Drug Administration and European Medical Agency warned that bradycardia could occur when amiodarone was administered in combination with sofosbuvir, but no case reports had been published. We report extreme bradycardia within 2 hrs after intake of sofosbuvir and daclatasvir by 2 patients receiving amiodarone. The first patient had a cardiac asystole 30 min after receiving sofosb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 3 publications
1
49
1
3
Order By: Relevance
“…This systematic review overviewed cardiac events, which are of concerning in patients treated with sofosbuvir according to the last reports 3,7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review overviewed cardiac events, which are of concerning in patients treated with sofosbuvir according to the last reports 3,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, there are events occurring in patients without amiodarone 7 . Third, the causality relationship between sofosbuvir (and amiodarone) and the onset of bradycardia in the case reports and case-series is methodologically doubtful 3,7 . Thus, a reasonable uncertainty exists regarding sofosbuvir and the risk of cardiac/arrhythmic/bradycardic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Another observation reported extreme bradycardia after first doses of sofosbuvir and daclatasvir and indicated that patients treated with amiodarone should be continuously monitored within the first 48 hours following the initiation of therapy with these DAAs. [36] Direct acting antiviral-related pharmacokinetic drug interactions Food increases the absorption of the all-oral paritaprevir/ ritonavir/ombitasvir plus dasabuvir, boceprevir and simeprevir, and so, it is recommended to take these medications with food. Fatty meals increase the absorption of telaprevir and asunaprevir.…”
Section: Pharmacologic Basis Of Direct Acting Antiviral Drug Interactionmentioning
confidence: 99%
“…The combination of ethinylestradiol with glecaprevir/pibrentasvir and velpatasvir/sofosbuvir + voxilaprevir can lead to ALT elevation and is therefore contraindicated [56, 59]. Last but not least DDI with the following medications need also to be kept in mind when treating with DAA: (1) amiodarone, (2) St. John’s wort, (3) rifampicin, (4) antiepileptic drugs, (5) antiretroviral medications and (6) psychotropic drugs [50, 64, 65]. …”
Section: Ddi As Complication In Hcv Therapymentioning
confidence: 99%